OROLBOʻYI OʻTLOQI-ALLYUVIAL TUPROQLARNING MIKROORGANIZMLAR TARQALISHINING YIL MAVSUMLARI HAMDA SHOʻRLANISH DARAJALARIGA KOʻRA OʻZGARISH DINAMIKASI - Shamuratova, G.M. (SCIENCE and SOCIETY, 2025)
The article examines the dynamics of changes in the distribution of microorganisms in meadow-alluvial soils of the Aral Sea region depending on the seasons and the degree of salinity. In this case, soil samples were taken and analyzed for the seasons of the year, determining the distribution of microorganisms in the soils of the Nukus massif with different degrees of salinity. Analysis results showed that as the salinity level increases, the number of microorganisms decreases. It has been established that microorganisms are more common in the upper layers of the soil and vary depending on the season.